THE PLACE OF ETHNONYMS IN THE LEXICON OF THE EPIC "ALPOMISH" - Khaitov Khusniddin Khasanovich (Galaxy International Interdisciplinary Research Journal, 2022)
This article presents a statement of opinions on the dialectal explanation of ethnonyms in the lexicon of the variants of the epic "Alpomish" Fazil Yoldosh oghli and Abdunazar Bakhshi. Examples of words meaning the names of clans, tribes and peoples found in the text of the epic are selected, and a dialectal descriptive explanation is given for each of them. Also, the words meaning the names of clans, tribes and peoples in the text of the epic have been scientifically and theoretically analyzed as dialectal words.